MATERIALS APPLICATION OF REMOTE SENSING IN MONITORING TASKS OF FOREST FIRES AND QUANTITATIVE EVALUATION OF VEGETATION - Зацерковний, В. І.; Тішаєв, І. В.; Шишенко, О. І. (Science-based technologies, 2016)
The forest sphere problems (issues) are considered. There is a focus made on the fact that forest territories of Ukraine suffer from massive human pressure. The main reasons for territories reduction is an impact of poor weather conditions, forest diseases, vermin damage, unbalanced system of forest management, abuse in the sphere of forest usage and forest fires. Despite of constant execution of prevention and precaution fire protection measures, huge forest areas suffer from fires, and this becomes a heavy load for country’s budgets. Apart from direct detection of fires, the evaluation of their strength and development forecast, the critical objective (task) is to monitor the parameters of the fire: area, framework perimeter and radiation power of the fire, determination of losses, quantitative estimation of vegetation change as well. The possibility of determination of areas that burned out during big forest fires allow to conduct inventory of forests condition after fires. An important economic and strategic task is the investigation of dynamic changes and condition of the forest. High informative value of observations from artificial satellites of earth provides a possibility to quickly and impartially evaluate stocks of forest resources and investigate changes which happened to them: fires appearance, losses estimations, the process of forest restoration on burned areas and logged areas, adjustment of forest damage estimations due to diseases and vermin, fires, detection of logged areas with further task to control them and their legitimacy, the inventory problem solving, evaluation of forest coverage of the territories, mapping of areas covered with forest and forest type structure. This slows to timely take measures in order to use forest resources efficiently and to prevent losses.